Efforts to Save the Universe: Muhammadiyah's Concern for the Environment - Harimurti, Shubhi Mahmashony; Alam, Shahbaz (Universitas Muhammadiyah Surakarta, 2024)
Muhammadiyah as a part of the civilization has a responsibility to spread the mercy. The organization that founded by KH Ahmad Dahlan is not carrying the theme